A Pragmatic Analysis of Efl Learners’ Social Media Interaction - Yunita Uswatun Khasanah (JETLe (Journal of English Language Teaching and Learning), 2019)
As a new and emerging venue of interaction, social media provide an ample opportunity for EFL learners to practice their English mastery and to enhance their socio-pragmatic awareness. However, even though some social media attempt to accommodate and mimic offline communications through their features, there are still technological and platform affordance and constraints that limit what users can do to get their message across. This situation makes a pragmatic analysis of online communication using offline measure a naïve endeavor. To confirm this notion, this paper borrows concepts from relevance theory pertaining to L1 and L2 pragmatics to reveal the patterns of online communication of 43 EFL learners in their social media interaction. The results show that there is a different pattern between online and offline interaction where they share a non-prototypical model of communication, the process of context and meaning construction, as well as their attempt to compensate for what the platform is lacking in accommodating their communication need.